Impact of emotions on academic performance and quality of life of Medical students (Research, Society and Development, 2021)
Quality of Life is a challenge for health practices, even more so in times of the COVID-19 pandemic. Entering higher education is part of one of the transition phases in human life and involves a series of adaptations. Students in the health field, especially those in medicine, as it is an integral course that requires many hours of dedication to their studies, suffer many pressures that can affect academic performance. Therefore, this study gathers information about the emotional factors that influence the quality of life of medical students in the form of an integrative review. We performed in PubMed, SciELO, BVS, and Academic Google databases using the descriptors: "Quality of Life" AND "Medical Students" for studies on this topic. The analyzes confirm that the pressures of academic life can hinder students' curricular development, either by affecting cognition or practical skills, in addition to reducing the sense of trust and inhibiting interpersonal relationships and emotional expression. Difficulty in paying attention during classes, not thinking, difficulty focusing, inability to complete tasks, risk of failure, and potential academic dropout increase considerably in these cases. Such factors, when present, are important indicators of emotional distress and have a considerable impact on the quality of life of medical students.